Proceedings 2001 ICRA. IEEE International Conference on Robotics and Automation (Cat. No.01CH37164)
DOI: 10.1109/robot.2001.933145
|View full text |Cite
|
Sign up to set email alerts
|

A de-coupled vibratory gyroscope using a mixed micro-machining technology

Abstract: This paper presents the highly reliable and wafer level vacuum packaged vertical micro-gyroscope with decoupled vibrating structures. In order to increase the sensitivity by exact tuning the resonant modes without instability problem, we devised two torsion springs for sensing mode in addition to four driving springs attached to outer gimbal. For the fabrication of the proposed gyroscope with high aspect ratio and wafer level vacuum packaging, we used the mixed micro-machining process which has the merits of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…The independent springs for driving and sensing modes are used to avoid the coupling effect that is caused by the mechanical interference between the driving and the sensing modes. Several authors have reported a similar structure of the MEMS gyroscope [11,12].…”
Section: Vibratory Mems Gyroscope Using the Soi Processmentioning
confidence: 93%
“…The independent springs for driving and sensing modes are used to avoid the coupling effect that is caused by the mechanical interference between the driving and the sensing modes. Several authors have reported a similar structure of the MEMS gyroscope [11,12].…”
Section: Vibratory Mems Gyroscope Using the Soi Processmentioning
confidence: 93%
“…There are still many labs researching on decoupling gyroscopes, for example, Yokohama Technical Center of Japan [34], UC Berkeley [35,36], Seoul University of Korea [37], Samsung company [38], and so on. The comparison of some parameters is listed in table 7.…”
Section: Micro-gyroscope Based On Coriolis Effectmentioning
confidence: 99%
“…The USA has successfully picked up electrostatic gyroscope signals of the GP-B satellite, which obtains 10 −4 order of magnitude In terms of processes, MEMS gyroscopes still mainly adopt MEMS micromachined fabrication technologies, which are comprised of bulk fabrication and surface fabrication. For those gyroscopes in laboratory level, scientific researchers generally adopt bulk micromachined fabrication [8,10,13,18,30,31,33,34,38,59], surface micromachined fabrication [9,14,24] and mixed micromachined fabrication [12,22] to manufacture gyroscopes. Mixed micromachined fabrication means that the whole process includes not only bulk fabrication but also surface fabrication, and that method varied according to different gyroscope structures.…”
Section: Evaluations On Micro-gyroscopesmentioning
confidence: 99%
“…A design of a decoupled vertical gyroscope has been announced. It was fabricated and tested to have the right operation [5].…”
Section: Introductionmentioning
confidence: 99%
“…The Coriolis force proportional to the angular velocity causes displacements in the vertical direction. If the natural frequency in the sensing mode matches that in the driving mode, the displacements are exaggerated and sensing is easy [5]. Therefore, it is important to match the natural frequencies of the two vibration modes [6,7].…”
Section: Introductionmentioning
confidence: 99%